Analisis Kualitatif Infrastruktur Jaringan Komputer dan Dukungannya terhadap Penggunaan Cloud Computing di SMPN 19 Kajang Bulukumba - Ulfa Laela Rambega (Journal of Innovative and Creativity, 2023)
This study aims to analyze the condition of the computer network infrastructure and the extent to which the infrastructure supports the implementation of cloud computing at SMPN 19 Kajang Bulukumba. This study uses a descriptive qualitative approach to describe and analyze the condition of the computer network infrastructure and its support for the implementation of cloud computing at SMPN 19 Kajang Bulukumba, with key informants such as the Principal, IT staff, ICT teachers, and school operators selected through purposive sampling techniques. Data were collected through semi-structured interviews, direct observation of network facilities and cloud-based learning activities, and documentation such as RPS and training reports. Data analysis was carried out using the Miles and Huberman model through inductive reduction, presentation, and drawing conclusions, with data validity strengthened through triangulation and member checks. This study found that the computer network infrastructure at SMPN 19 Kajang Bulukumba has been built since 2019 with the support of the Education Office, including LAN networks, fiber optic internet connections, and supporting devices, although there are still obstacles in Wi-Fi coverage and hardware quality. Cloud computing such as Google Classroom and Google Drive have been used since the pandemic, but their implementation has not been maximized due to the limitations of teachers' digital literacy and students' devices. Observations show that some computers are outdated, Wi-Fi distribution is uneven, and server rooms are not equipped with good cooling systems and cable management. Although school documentation reflects digital development efforts, teacher participation in training is still limited, so the existing infrastructure only supports cloud computing to a limited extent and requires further improvement.